2007
DOI: 10.1016/j.applthermaleng.2007.04.007
|View full text |Cite
|
Sign up to set email alerts
|

CO2 capture study in advanced integrated gasification combined cycle

Abstract: This paper presents the results of technical and economic studies in order to evaluate, in the French context, the future production cost of electricity from IGCC coal power plants with CO 2 capture and the resulting cost per tonne of CO 2 avoided. The economic evaluation shows that the total cost of base load electricity produced in France by coal IGCC power plants with CO 2 capture could be increased by 39% for 'classical' IGCC and 28% for 'advanced' IGCC. The cost per tonne of avoided CO 2 is lower by 18% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…Those slags play a major role in the design of CO 2 -emissionreduced power plants in which coal is gasified with the help of an appropriate reactor (Integrated Gasification Combined Cycle [20,21]). Due to extremely high temperatures in this gasification step, ash particles from the coal occur in liquid form (slag) and represent a danger for the subsequent gas turbine process.…”
Section: Application To Surface Tension Measurements Of Coal Ash Slagsmentioning
confidence: 99%
“…Those slags play a major role in the design of CO 2 -emissionreduced power plants in which coal is gasified with the help of an appropriate reactor (Integrated Gasification Combined Cycle [20,21]). Due to extremely high temperatures in this gasification step, ash particles from the coal occur in liquid form (slag) and represent a danger for the subsequent gas turbine process.…”
Section: Application To Surface Tension Measurements Of Coal Ash Slagsmentioning
confidence: 99%
“…It was reported that MDEA can deliver performance comparable with the physical absorption processes when the pressure of the gas stream is not very high. 10 Once the sulfur is removed, the clean syngas can be sent to the power generation block for combustion. Because CO is still in the syngas stream, carbon in the coal is not captured in this scenario and will be emitted from the combustor exhaust in the form of CO 2 .…”
Section: Gas Cleaning and Conditioning Blockmentioning
confidence: 99%
“…Use of porous ceramics enables low-cost and maintenance-free continuous processing of gas separation filters. Therefore, it is expected that application of these filters to energy and environmental engineering, e.g., carbon dioxide capture and storage (CCS), 53) integrated coal gasification combined cycle (IGCC), 54) and so on, will intensify. Instruments designed for particle dispersion have been developed on the basis of dispersion data.…”
Section: Gas Separation Filtersmentioning
confidence: 99%